2011
DOI: 10.1258/hsmr.2011.011011
|View full text |Cite
|
Sign up to set email alerts
|

A professional challenge: the development of skill-mix in UK primary care dentistry

Abstract: The future health-care workforce and the changing skill-mix within occupational teams is a current topic of discussion. This paper contributes to the skill-mix debate by focusing on UK primary care dentistry, revealing unintended as well as intended consequences of a modularized, technocratic view of dentistry. In part one, relevant literature about dental therapists and skill-mix in dentistry is organized into a framework used to review factors operating at macro, meso and micro levels. Part two considers the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Medical specialists working at the clinics have sufficient idle time; hence, health workforce tends to be under loaded. Bullock and Firmstone (2011) study on UK's dental care found that education and training of dentist influence patient and dentist reported outcomes. Spilsbury et al (2011) found that health centres that focus on increasing the number of nurses and doctors are not able to focus on factors that affect health care service quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Medical specialists working at the clinics have sufficient idle time; hence, health workforce tends to be under loaded. Bullock and Firmstone (2011) study on UK's dental care found that education and training of dentist influence patient and dentist reported outcomes. Spilsbury et al (2011) found that health centres that focus on increasing the number of nurses and doctors are not able to focus on factors that affect health care service quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the reasons given for not extending DCPs' roles cited practice characteristics (sufficient cover for work already or no demand due to narrow scope of practice); 11 lack of staff to support extension; 9 and a lack of space within the practice or finances to adapt current spaces. 4,9,12 The financial issues around funding and payment were also listed as a barrier to role extension. 9,12,13 The types of remuneration system are influenced by political and professional cultures 14 and this in turn affects the supply of services and patient demand.…”
Section: Practice Culturesmentioning
confidence: 99%
“…Part-time hours may allow for the employment of a therapist in a practice with limited surgery space or with a dentist who is mindful of the professional boundaries between the two roles. 4 Until funding issues are addressed GDPs need to carefully formulate payment plans for therapists; under the current system of remuneration employing DH/ CTHs on an hourly rate may be the best way to improve profitability. 12 However, of those practices which had extended DCPs duties, single-handed practices were the second most likely to have extended roles, which is at odds with Newton and Gibbons' finding that single-handed practitioners were least likely to report that they would employ a therapist.…”
Section: Part-time Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…This echoes evidence from elsewhere of tension between 'acknowledging that less qualified practitioners can contribute directly to dental treatment and the unwelcome consequences of a modularised approach'. 152 Intuitively, the delegation of treatment to staff specialised in only a specific range of treatments could reduce costs and increase access to care. 132 The acceptability of the blended/incentive-driven contract to dental providers is clearly important, not least because of the financial implications.…”
mentioning
confidence: 99%